A structure scheme to reduce the influence of the accelerometer inner lever-arm effect on tri-axis inertial navigation systems. (24th March 2021) - Yang, Shenglin; Hu, Xiaomao; Wang, Xiaodan; Li, Dechun
Abstract: The accelerometer inner lever-arm effect is a significant error source for high-precision inertial navigation systems (INSs) and has a marked influence on the speed accuracy—a critical technical index of high-precision weapon systems. Rotation modulation technology is widely applied to reduce the errors of high-precision INS. However, this method fails to work for the inner lever-arm effect. Furthermore, variations in the rotation angular velocity and acceleration during modulation alter the inner lever-arm effect, further complicating the compensation of errors. System self-calibration is currently the principle method adopted to deal with the inner lever-arm effect, yet calculation errors result in residual estimations at the millimeter-level for the inner lever-arm. Such a residual will cause obvious speed errors for high-precision INS, which typically turns over the inertial measurement unit via the rotation modulation. This consequently makes it difficult to fully meet the requirements of high-precision weapon systems. In the current paper, we propose an accelerometer geometric space scheme based on the calculations and structural characteristics of a tri-axis INS. Through a simple structure arrangement, we demonstrate the complete theoretical elimination of the inner lever-arm effect in the absence of complex calibration and compensation processes. The only residual error of the inner lever-arm in the proposed scheme is the accumulated geometric tolerance with a value less than 0.2 mm. Semi-physical simulation results reveal the ability of our scheme to directly reduce the magnitude of the system speed error from 10 −2 to 10 −5 . Moreover, the speed fluctuation disappears during the modulation rolling process, thus fully meeting the requirements of high-precision weapon systems.